1993
DOI: 10.1007/bf01374586
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions in a homogeneous electric field: the (HF)2 complex

Abstract: Summary. The interaction energy of two HF molecules, subjected to a static external field, is analyzed. The analysis aims at the elaboration of simple expressions able to reproduce environmental and substitution effects on noncovalent molecular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…All the simulations were carried out with AMBER 5.0 22 employing the second generation force field, by Cornell et al 12. This choice was dictated by the fact that previous studies of ours 23, 24, as well as of other authors 13, showed a satisfactory performance of this force field in the evaluation of the stability of either H‐bonded or stacked complexes. Furthermore, the results obtained with AMBER turned out to be even better than those computed with other force fields 13, 24.…”
Section: Computational Detailsmentioning
confidence: 99%
“…All the simulations were carried out with AMBER 5.0 22 employing the second generation force field, by Cornell et al 12. This choice was dictated by the fact that previous studies of ours 23, 24, as well as of other authors 13, showed a satisfactory performance of this force field in the evaluation of the stability of either H‐bonded or stacked complexes. Furthermore, the results obtained with AMBER turned out to be even better than those computed with other force fields 13, 24.…”
Section: Computational Detailsmentioning
confidence: 99%
“…This investigation, however, directly pertains to the vast literature, which we are not going to review, concerning the electronic and geometrical properties of bimolecular adducts and to the debate about stacked and T-shaped positions, in the gas phase , or in solution, , even inside a single molecule. In addition, it constitutes a natural continuation of our previous studies on H-bonded dimers in the gas phase and in the presence of an external field . For these reasons, the highest level ab initio calculations compatible with the size of the complexes under scrutiny were used, and the counterpoise correction to the basis set superposition error (BSSE) was introduced for test cases in both the HF and MP2 correlated wave functions.…”
Section: Introductionmentioning
confidence: 99%
“…When a molecule is placed under the effect of an applied electric field, its electronic cloud is modified, its nuclear positions are changed, and its vibrational motion is perturbed. [14][15][16][17][18][19][20][21][22][23][24][25][26] All these induced changes can be explained in terms of different contributions to the electrical properties, namely, electronic (P el ), nuclear relaxation (P nr ) and vibrational (P vib ).…”
Section: Introductionmentioning
confidence: 99%